TEMPO-functionalized zinc phthalocyanine: synthesis, magnetic properties, and its utility for electrochemical sensing of ascorbic acid - Korkut, Sibel Eken; Akyuz, Duygu; Ozdogan, Kemal; Yerli, Yusuf; Koca, Atif; Sener, M. Kasim (ROYAL SOC CHEMISTRY, 2016)
Zinc(II) phthalocyanine (TEMPO-ZnPc), peripherally functionalized with 2,2,6,6-tetramethyl-1-piperidinyloxy (TEMPO) radicals is synthesized and its magneto structural and electrochemical behaviors are investigated. TEMPO-ZnPc shows multi-electron ring based reduction reactions and a TEMPO based oxidation reaction. Spectroelectrochemical measurements support these peak assignments. TEMPO-ZnPc is tested as a homogeneous and heterogeneous ascorbic acid (AA) sensor. Disappearance of TEMPO-ZnPc based reduction processes and the observation of new waves at around 0 and 1.20 V with respect to increasing AA concentration indicate the interaction of TEMPO-ZnPc with AA and usability of the complex as an electrochemical AA sensor. For practical usage as heterogeneous electrocatalysts for AA sensing, a glassy carbon electrode (GCE) is coated with TEMPO-ZnPc (GCE/TEMPO-ZnPc) and this modified electrode is tested as a heterogeneous AA sensor. The redox peak of GCE/TEMPO-ZnPc at 0.81 V decreases the peak current while a new wave is observed at 0.65 V during the titration of the electrolyte with AA. GCE/TEMPO-ZnPc sense AA with 1.75 x 10(-6) mol dm(-3) LOD with a sensitivity of 1.89 x 10(3) A cm mol(-1).
Keywords: CARBON NANOTUBES; ELECTRODES; OXIDATION; RADICALS; SPECTROELECTROCHEMISTRY; NANOPARTICLES; COMPLEXES; SENSORS; Chemistry